Genome-wide Screens for Sensitivity to Ionizing Radiation Identify the Fission Yeast Nonhomologous End Joining Factor Xrc4. Issue 7 (1st July 2014) - Li, Jun; Yu, Yang; Suo, Fang; Sun, Ling-Ling; Zhao, Dan; Du, Li-Lin
Abstract: Nonhomologous end joining (NHEJ) is the main means for repairing DNA double-strand breaks (DSBs) in human cells. Molecular understanding of NHEJ has benefited from analyses in the budding yeast Saccharomyces cerevisiae and the fission yeast Schizosaccharomyces pombe . In human cells, the DNA ligation reaction of the classical NHEJ pathway is carried out by a protein complex composed of DNA ligase IV (LigIV) and XRCC4. In S. cerevisiae, this reaction is catalyzed by a homologous complex composed of Dnl4 and Lif1 . Intriguingly, no homolog of XRCC4 has been found in S. pombe, raising the possibility that such a factor may not always be required for classical NHEJ. Here, through screening the ionizing radiation (IR) sensitivity phenotype of a genome-wide fission yeast deletion collection in both the vegetative growth state and the spore state, we identify Xrc4, a highly divergent homolog of human XRCC4. Like other fission yeast NHEJ factors, Xrc4 is critically important for IR resistance of spores, in which no homologous recombination templates are available. Using both extrachromosomal and chromosomal DSB repair assays, we show that Xrc4 is essential for classical NHEJ. Exogenously expressed Xrc4 colocalizes with the LigIV homolog Lig4 at the chromatin region of the nucleus in a mutually dependent manner. Furthermore, like their human counterparts, Xrc4 and Lig4 interact with each other and this interaction requires the inter-BRCT linker and the second BRCT domain of Lig4. Our discovery of Xrc4 suggests that an XRCC4 family protein is universally required for classical NHEJ in eukaryotes.